The Impact of Staff Training on Enhnacing Customer Serive in the Resturant Industry: A Study of Birendra Birendranaagr, Surkhet - Silwal, Bikash (Journal of Entrepreneurship & Management Studies, 2025)
Customer service is a central driver of success in the restaurant industry, especially in growing urban areas where competition and guest expectations are rising. Staff training has emerged as a critical factor influencing how consistently and effectively service is delivered. This study examines how different components of staff training i.e., training resources, employee perceptions of training, and training methods, shape customer service performance in restaurants operating in Birendranagar, Surkhet. A quantitative research design was used to explore the relationship between training practices and customer service outcomes. Data were collected from restaurant employees and customers using a structured questionnaire that captured key aspects of training and service performance. SPSS statistical tool were performed to identify patterns and measure the predictive influence of training-related variables. Findings indicate that the availability of training resources and employees’ positive perceptions of training strongly support higher levels of customer service. Although various training methods were in use across restaurants, their direct influence on service performance was less pronounced compared to resource availability and employee attitudes. Overall, the study highlights that well-supported and meaningful training contributes substantially to enhanced service encounters. The research emphasizes the need for restaurants to invest in clear, structured, and resource-rich training systems. When employees view training as valuable and are provided with adequate tools to learn, customer service improves noticeably. Strengthening training frameworks can therefore play an important role in elevating service quality and ensuring sustainable growth in the restaurant sector of emerging urban areas.